2018
DOI: 10.15171/apb.2018.058
|View full text |Cite
|
Sign up to set email alerts
|

Determining Abuse Deterrence Performance of Poly (ethylene oxide) Using a Factorial Design

Abstract: Purpose: The purpose of this study was to determine the effects of thermal processing and antioxidant formulation variables on the abuse deterrence performance of a high molecular weight poly(ethylene oxide) (PEO) polymer.Methods: A 24 factorial design with one categorical factor (antioxidant type) and three continuous factors (curing time, curing temperature, % antioxidant) was used. Abuse deterrence performance was evaluated using solution viscosity, surface melting temperature, and mechanical strength. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…FT-IR spectrum of SOL showed characteristic bands at 2922 cm −1 (C-H), 2857 cm −1 (C-H), 1740 cm −1 (C=O of the carboxylic group) and 1633 cm −1 (C=O of the amide group) [ 46 , 47 ]. FT-IR spectrum of PEO showed characteristic bands at 2888 cm −1 (C-H), 1240 cm −1 (O-H), 1093 cm −1 (C-O) and 1059 cm −1 (C-O) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…FT-IR spectrum of SOL showed characteristic bands at 2922 cm −1 (C-H), 2857 cm −1 (C-H), 1740 cm −1 (C=O of the carboxylic group) and 1633 cm −1 (C=O of the amide group) [ 46 , 47 ]. FT-IR spectrum of PEO showed characteristic bands at 2888 cm −1 (C-H), 1240 cm −1 (O-H), 1093 cm −1 (C-O) and 1059 cm −1 (C-O) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the injectability force was observed to be from 2.4 ± 0.4 to 10.8 ± 0.4, 3.5 ± 0.2 to 16.1 ± 0.3 and 2.5 ± 0.4 to 9.1 ± 0.7, respectively for static, agitated, and thermally manipulated pellets. The decrease in resistance to syringe (pulling) and injection (pushing) for the PEO formulation (F1) after thermal manipulation may be due to a reduction in solution viscosity, degradation, and a shortened polymer chain end-to-end distance of PEO after thermal treatment (Joshi et al, 2018). Thus, reduced pulling and pushing forces could be attributed to ease of syringreability and injectability, which led to compromising the IV abuse deterrent potential.…”
Section: Syringeability and Injectabilitymentioning
confidence: 99%
“…Thus, the reduction in solution viscosity of the F1 formulation, after thermal manipulation, was due to random chain scission of the PEO structure into smaller fragments at high temperature. Joshi et al, 2018 reported the effect of temperature and concentration of PEO on the solution viscosity. The reduction in solution viscosity was observed as the temperature increased up to 110°C and a further increase in temperature from 110°C to 150°C resulted in a sharp drop in solution viscosity.…”
Section: Viscosity Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Thermal manipulation is one of the major tools used by abusers to overcome crush resistance and extraction resistance of drug products. 7 Heating high molecular weight PEO close to its degradation temperature may change its chemical structure 8 and diminish crush resistance. Additionally, the high viscosity built up by PEO in water or hydroalcoholic solutions may be significantly lost if the original solid PEO is heated up to its degradation temperature before preparing its aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%